Circumflex coronary artery injury after mitral valve surgery: A report of four cases and comprehensive review of the literature. Issue 1 (19th February 2016) - Hiltrop, Nick; Bennett, Johan; Desmet, Walter
Abstract : As the LCx is closely related to the mitral valve annulus, it is susceptible to perioperative injury. Various underlying mechanisms, predisposing factors, and therapeutic strategies have been suggested but disagreement exists. Using a MeSH terms‐based PubMed search, 44 cases of mitral valve surgery‐related LCx injury were detected, including our 4 cases. We provide a comprehensive review of current knowledge regarding mitral valve surgery‐related left circumflex coronary artery (LCx) injury. Preoperative coronary angiography was performed in 55% ( n  = 24). Coronary abnormalities were present in 11% ( n  = 5). Coronary dominance was reported in 73% ( n  = 32), predominantly showing left (69%, n  = 22) or balanced (19%, n  = 6) circulations. Right coronary dominance was present in 12% ( n  = 4). Ischemia was detected in the perioperative or early postoperative phase in 86% ( n  = 30). Delayed symptoms were present in 14% ( n  = 5). Echocardiography demonstrated new regional wall motion abnormalities in 80% ( n  = 24), but was negative in 20% ( n  = 6) despite coronary compromise. Electrocardiography showed myocardial ischemia in 97% ( n  = 34), including regional ST‐segment elevations in 68% ( n  = 23). Primary treatment was surgical in 42% ( n  = 15) and percutaneous in 58% ( n  = 21), reporting success ratios of 87% ( n  = 13) and 81% ( n  = 17), respectively. We confirm an augmented risk of mitral valve surgery‐related LCx injury in balanced or left‐dominant coronary circulations. Preoperative knowledge of coronary anatomy does not preclude LCx injury. An anomalous LCx arising from the right coronary cusp was identified as a possible specific high‐risk entity. Electrocardiographic monitoring and intraoperative echocardiography remain paramount to ensure a timely diagnosis and treatment. © 2016 Wiley Periodicals, Inc.